Incidence of late-onset hemorrhagic cystitis and its effect on PFS in acute leukemia patients after haplo-PBSCT: The 5-year single-center data - Yuan, Hailong; Chen, Gang; Xu, Jianli; Yang, Ruixue; Muhashi, Maria; Aizezi, Gulibadanmu; Jiang, Ming (Frontiers in Oncology, 2022)
We conducted a single-center 5-year retrospective study on the occurrence of hemorrhagic cystitis (HC) and its effect on survival after haploid high-dose peripheral blood stem cell transplantation (haplo-PBSCT) in patients with acute leukemia. We retrospectively analyzed 153 patients with acute leukemia who were treated with non-in vitro T-cell depleted haplo-PBSCT and myeloablative conditioning regimen. All patients were followed up for more than 180 days after transplantation. HC occurrence and its effect on long-term progression free survival (PFS) were retrospectively analyzed. Totally, 64 out of 153 patients had late onset HC (LOHC). No early onset HC occurred. The median onset time was 38.5 (17-163) days after transplantation. The cumulative incidence of LOHC was 41.8%. The cumulative incidence of LOHC in patients under 27 years old (50.0%) and in ALL patients (54.1%) was significantly higher than that in patients over 27 years old (34.5%) and in AML patients (36.9%), respectively. The cumulative incidence of mild LOHC was 44.2% and that of severe LOHC was 28.6%. However, urine copies of BK virus were not related to LOHC duration. There was no significant difference in 3-year expected PFS between AML and ALL patients with and without LOHC, or between LOHC duration more than and less than 38.5 days (P>0.05). Conclusively, LOHC incidence is higher in patients under 27 years old and in ALL patients. LOHC occurrence is related to urine BK virus copy, but not blood BK virus load. LOHC duration and severity has no significant effect on PFS.